Outcome of pregnancy in patients who suffered first trimester bleeding per vaginum - V Shukla, Jitendra; Gilitwala, Prakruti; Sethi, Parth; Chavada, Meet (Journal of Neonatal Surgery, 2025)
About one fourth of all gravid patients suffer from first trimester bleeding p/v. Since ours is a rural tertiary health care centre catering MCH services to surrounding rural population, we manage many patients with first trimester bleeding per vaginum. We were inspired to carry out the study. In this study we found that patients who had closed os with present cardiac activity when treated properly in time got cured and carried pregnancy to term to have a favourable outcome.